Peran Brand Trust Memediasi Pengaruh Electronic Word of Mouth terhadap Keputusan Pembelian Konsumen Iclothes Bali: (Studi pada Aplikasi Shopee) - Putri Swandewi, Dewa Ayu; Ary Pratiwi, Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Technological developments make it easier for consumers to buy the clothes they need. The type of marketing that is currently popular is sales through online shop applications that are well-known in Indonesia, one of which is Shopee. The purpose of this study was to determine the role of brand trust in mediating the effect of electronic word of mouth on consumer purchasing decisions of Iclothes Bali. This research was conducted on Iclothes Bali on the Shopee application. The number of samples used was 75 respondents with the probability sampling method. Data analysis techniques use structural equation modeling (SEM). This study uses a quantitative analysis approach that adopts Partial Least Square (PLS). Based on the results of the analysis it was found that electronic word of mouth had a positive and significant influence on the Trus brand. Electronic word of mouth has a positive and significant impact on purchasing decisions. Brand Trust has a positive and significant influence on purchasing decisions. Brand trust is able to mediate the influence of electronic word of mouth on purchasing decisions, which has a positive and significant influence. Suggestions in this study are to increase advertising, ensure transaction security, improve product quality. Future researchers are expected to add to the construct to be able to identify more deeply about purchasing decisions.